Assurance Services for Sustainability Reports: Standards and Empirical Evidence - Manetti, Giacomo (Journal of business ethics, 2009)
This article contributes to the growing scholarship on the topic of assurance services for sustainability reports. We first synthetically illustrate the main international standards for the implementation of assurance services regarding the subject documents. The second part of our article is an empirical analysis of reports drawn up on the basis of the current Global Reporting Initiative 2006 guidelines, and looks at how effectively these standards have been implemented, analyzing the different typologies of assurance statement.